Usability Analysis of Atma Jaya Catholic University E-Learning Based on Human Computer Interaction - Henoch Juli Christanto; Stephen Aprius Sutresno; Vincentius Setiawan Suandi (Universitas Bina Darma, 2023)
E-learning UAJ is a system provided by Unika Atma Jaya to facilitate the learning process for both students and lecturers. However, this system is still rarely used, especially among engineering faculties. This forms the basis for conducting the following analysis. The purpose of this research is to measure the level of usability of the UAJ e-learning system. Usability analysis is carried out using five components of usability outlined by Jakob Nielsen: Learnability, Efficiency, Memorability, Errors, and Satisfaction. The indicators within these five components are then compiled into a questionnaire, which will be distributed to active lecturers and students across all faculties who utilize the UAJ e-learning platform. This study employs a Likert scale with five categories, ranging from category 1 indicating